Novel use of intravascular lithotripsy for vertebral artery stenosis: A case report - Orlando Diaz, MD; Jochen Gerstner-Saucedo, MD; Isabel Carmona (Radiology Case Reports, 2025)
Severe vertebral artery stenosis complicated by dense calcification represents a significant surgical challenge, particularly when accompanied by limited collateral circulation. Traditional high-pressure balloon angioplasty is an adequate option. However, it can increase the risk of vascular injury and it often achieves inadequate stent expansion. Intravascular lithotripsy (IVL) has recently been proposed as an alternative method for safely fracturing calcified plaques with acoustic pressure waves at lower balloon pressures. We report a symptomatic patient where IVL was used for predilation during a vertebral artery stenting from a femoral approach. Initially, diagnostic imaging revealed a hypoplastic left vertebral artery terminating in the posterior inferior cerebellar artery (PICA), as well as critical stenosis caused by heavily calcified plaque in the V2 segment of the right vertebral artery. The patient underwent further postdilation and stent deployment following a successful endovascular procedure with IVL at an inflation pressure of 2 atm. The patient experienced complete symptom resolution and recovered without any complications. This case highlights the potential benefits of IVL over traditional angioplasty techniques by demonstrating its efficacy and safety in treating heavily calcified vertebral artery stenosis.